Effect of plant geometry on growth and yield of corn in the rice-corn cropping system - Chauhan, Bhagirath S.; Opeña, Jhoana L. (Scientific Research Publishing, Inc., 2013)
The rice-corn cropping system is increasing in Asia in response to increased demand of corn for feed. A field study was conducted to evaluate the effect of plant geometry (row and plant to plant spacing: 50 × 20, 50 × 30, 75 × 20, and 75 × 30 cm) on growth and yield of corn. Plant height and leaf production per plant were not influenced by the plant geometry. Spacing, however, influenced leaf area, aboveground shoot biomass, and yield of corn per unit area. Highest leaf area, shoot biomass, and yield (8.2 t·ha-1) were produced by plants grown at 50 × 20 cm spacing. The results of this study suggest that narrow rows and plant to plant spacing may increase grain yield by increasing crop growth rates. Plant geometry could be modified to improve yield of corn in the rice-corn cropping system, and thereby increase productivity of the system.